Science Interest Detection Using Computerized Adaptive Testing Based on Fuzzy Item Response Theory - Wulandari, Fitri (Fakultas Sains dan Teknologi, Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Choosing a major or interest at the beginning of High School is a very important process for the future development of students. A test may be performed to determine the learner's ability in a particular field In this research, an interest test was developed to determine the students' ability in science. Students will be measured for their cognitive ability in Mathematics and Science subjects for junior high school level. The research was developed using an adaptive test system called Computerized Adaptive Testing (CAT). CAT is an adaptive media based model, test participants will receive the test according to their ability. The test item selection procedure uses the fuzzy algorithm using item difficulty parameters, item strengths and participants' response data as input data. While the rule or procedure for terminating the test is done with the maximum likelihood estimation method, MLE. Based on the test results, each student received different test items according to their ability level and the difficulty indexs that received by the students according to the characteristics of the item information. Therefore, the CAT program with the fuzzy item response theory can be used as a support for measuring the students' ability and interest in a major.